Pengaruh Kemudahan Pembayaran Digital Terhadap Perilaku Konsumtif - Susilowati, Nenden; Surbakti, Zefania Pasti; Fitriyani, Nanda; Zakiya, Mimin; Ariyanto, Ardi (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
This study aims to analyze the effect of cashless lifestyle transformation and Shopeepay usage on the consumptive behavior of students. This study uses a quantitative approach with a population consisting of all members of UKMF INSPIRE FEB UNY with a sample of 47 students selected through purposive sampling. The collected data was then analyzed using multiple regression tests to measure the relationship between these variables. The results of the study show a significant positive impact of ShopeePay usage on student consumption behavior; the more often students use ShopeePay, the more likely they are to engage in consumptive behavior. Conversely, the transformation to a cashless lifestyle has a negative impact because there is a risk of uncontrolled consumption, especially among students who are prone to impulsive spending. Therefore, it is recommended that ShopeePay develop reminder features or spending limits to help students manage their finances more wisely and minimize impulsive consumption behavior.